The Missing News : Filters and Blind Spots in Canada's Press - Hackett, Robert A. (Book collections on Project MUSE., 2000)
Published Under the Garamond Imprint North Americans now live in a highly complex media environment where newspapers are still immensely important vehicles for democratic communication. No other mass medium offers the same combined possibilities for accessibility, in-depth analysis, diversity of views, and sustained reflection on important political and economic issues. But do newspapers in Canada really report an adequate range of views and issues? The authors argue that as significant as what is reported are the stories that are not reported, or "buried." What are the filters and blind spots that determine what gets into print... and what doesn't? The authors believe that journalism's most important tasks in a democratic society include holding those in power accountable, and giving voice even to those without wealth or political influence. The Missing News shows us that Canadians have reason to be concerned.